Displacement of pacemaker leads--a 10-year survey. - Brewster, G M (1979)
Displacement of endocardial pacemaker leads from the initial site at the time of implantation is a major cause of unpredictable pacemaker failure. In this survey, we have made a retrospective study of the effectiveness of the attempts made by two manufacturers to design leads to reduce the frequency of this occurrence. The cumulative displacement records of 5 types of leads (Medtronic types 5818, 6904, 6901, and 6950, and Cardiac Pacemakers Inc. type 4210) have been studied, and show that Medtronic 5818 and 6950, and CPI 4210 leads are superior in this respect.